Results of screening a group of otolaryngological patients for HIV infection - B C Ezeanolue (International Journal of Medicine and Health Development, 2001)
Objective: To document the result of screening a group of Otolaryngologic patients in Enugu for human immunodefficieacy viras(HIV) infection with emphasis on the clinical features of these patients and the Otolaryngologic diseases that the HIV seropositive patients are suffering from. Patients and Method: A prospective study of patients attending the Otolaryngology service Units at the University of Nigeria Teaching Hospital and Balsam Clinics both in Enugu. These patients were screened for HIV. Results: Thirty patients from a screened 265 patients tested positive to the presence of HIV antibodies in their sera. They were 16 males and 14 females with mean age of 25.2 years. Presentiag disease distribution by anatomic/subspecialty sites is Otology 5, Rhinology 6, Laryngology 11, and head and neck 8 patients. Chronic suppurative otitis media (5), cervical lymphadenopathy (4) and sinusitis (4) are the most common diseases. Conclusion: The most common factor associated with acquisition of HIV infection among our group of Otolaryngologic patients is heterosexual activities followed by foeto-maternal and blood transfusions. HIV infected patients present to the Otolaryngologist with the same disease pattern as the HlV-non-infected patients.